Q: How do you factor 4x2 plus 12x plus 9 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4(x + 2)(x + 1)

4x2 + 12x + 5 = (2x + 1)(2x + 5).

Only if the value of c is 9 because:- 4x2+12x+9 = (2x+3)(2x+3)

4x2+12x = 4x(x+3) when factored

-((4x + 1)(x - 1))

Related questions

There are four solutions to 9x4 plus 27x3 - 4x2 - 12x equals 0. One of the solutions is x = -3.

4x2 = -12x, divide both sides by 4x: x = -3

4(x + 2)(x + 1)

2(4x2 + 6x - 1)

4x2 + 12x + 5 = (2x + 1)(2x + 5).

4x2 - 12x + 9 = 5; whence, 2x - 3 = ±√5, and 2x = 3 ±√5. Therefore, x = ½ (3 ±√5).

4x

Only if the value of c is 9 because:- 4x2+12x+9 = (2x+3)(2x+3)

4x2+12x = 4x(x+3) when factored

12x * 4x2 = 48x3

Jjg

-((4x + 1)(x - 1))